RANCANG BANGUN MODEL KONTROL AKSES DINAMIS BERBASIS KONTEKS PADA ARSITEKTUR ZERO TRUST - Vega S. Meliala, Ruth Amelia; Kiswanto, Dedy; Harahap, Salsa Nabila; Dly, Revidamurti (P3M STMIK Profesional Makassar, 2026)
The rapid development of digital systems and interconnected environments has created new challenges in securing data. Traditional perimeter-based security models are no longer adequate to protect sensitive information from internal and external threats. This study proposes the design and implementation of a Context-Based Dynamic Access Control Model within the Zero Trust Architecture (ZTA) framework. The proposed system integrates contextual authentication, adaptive risk evaluation, and a dynamic policy engine to implement more granular access control in multi-user web applications. The prototype was developed using Node.js, Express.js, and MySQL, featuring multi-factor authentication, contextual verification via OTP, session management, and security notifications.The test results indicate that the system is capable of detecting changes in access context, enforcing re-authentication, and recording all user activities for auditing and anomaly detection purposes. The integration of contextual authentication, adaptive access control, and Zero Trust principles has been proven to enhance data protection and user accountability without reducing system usability..